Key Factors Impacting the Chemical Engineering Skill Pool in the South African Economy - Gina, Dumisa Cornelius (My University, 2012)
For many years South Africa was isolated from the world economy by political sanctions. This period crippled the ability of the economy to compete at a global level. The year 1994 marked the end of these trade sanctions and the beginning of international trade. South Africa had to start producing enough goods to supply the local market as well as export to other countries and to compete efficiently in this new arena. These productivity initiatives had to be supported by the right set of processing skills. Chemical engineering is at the heart of any large-scale industrial production. This study explores the key factors that impact on the chemical engineering skill pool in the South African economy. Interviews were conducted by the researcher with leaders in the South African chemical engineering industry as well as lead chemical engineering researchers in the country. A semi-structured interview schedule was used. The research showed that the key factors that impact on the chemical engineering skill pool in the South African economy are:gender stereotypes; inadequate contact between engineers through professional bodies; poor quality of teaching maths and science at school level; poor career guidance systems; poor marketing of the career at school and university level; poor funding and subsidies from government and the private sector; improper government policies and practices; poor remuneration for chemical engineers; and a lack of the right role models for scholars. Other factors identified include: HIV/AIDS infection; poverty; the nature of the chemical engineering work environment; the poor communication skills of previously disadvantaged students; the poor culture of learning; inadequate government leadership and co-ordination strategies; poor skills transfer and mentorship systems; as well as equity considerations, given the country’s history. The government has the ultimate role to put a proper structure in place to enable economic development. There is also a need for the government to engage all stakeholders in developing socio-political systems, economic systems, and legal systems to address the chemical engineering skills shortage in the country.
MBA thesis - WBS
Keywords: Productivity; Chemical industry; Skills development